THE ROLE PLAYED BY HUMAN DIGNITY IN RELIGIOUS DISCRIMINATION DISPUTES - Radley Henrico (Obiter, 2014)
Intrinsic to being human is the fact that we all have the right to human dignity – to self-worth, autonomy and the ability of self-determination. When dealing with religious discrimination, by default notions of inequality and more specifically unfair or disadvantaged discrimination come to the fore. In the assessment of such discrimination disputes it is interesting to note the extent to which the courts have viewed equality through the prism of human dignity. In this sense human dignity canbe said to take central stage so-to-speak in the arena of discrimination dispute resolution. The rationale for this must be premised on the fact that human dignity is far more than just a constitutional right; it is an imperative that jurisprudentiallyattaches itself to the fact that unfair discrimination on the ground of religion impacts adversely on what and who we are as individuals.